2019
DOI: 10.1126/sciadv.aay0244
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and composition play distinct and complementary roles in the tolerance of plantar skin to mechanical load

Abstract: Plantar skin on the soles of the feet has a distinct morphology and composition that is thought to enhance its tolerance to mechanical loads, although the individual contributions of morphology and composition have never been quantified. Here, we combine multiscale mechanical testing and computational models of load bearing to quantify the mechanical environment of both plantar and nonplantar skin under load. We find that morphology and composition play distinct and complementary roles in plantar skin’s load t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 49 publications
1
36
1
Order By: Relevance
“…The influence of the morphology and composition of plantar skin on the tolerance to load has been studied [52]. Plantar SC was found to be a factor of 16 thicker than the SC from non-plantar skin, with greater interdigitation between the epidermis and dermis and with a 2.1 increase in fluorescence intensity of desmoglein 1, a key component of CDs.…”
Section: Keratins: Role In Cell Mechanical Strengthmentioning
confidence: 99%
“…The influence of the morphology and composition of plantar skin on the tolerance to load has been studied [52]. Plantar SC was found to be a factor of 16 thicker than the SC from non-plantar skin, with greater interdigitation between the epidermis and dermis and with a 2.1 increase in fluorescence intensity of desmoglein 1, a key component of CDs.…”
Section: Keratins: Role In Cell Mechanical Strengthmentioning
confidence: 99%
“…Reinforcing this hypothesis are results of a study showing that mechanical stretching of the skin in a porcine model induced integrin β1 subunit upregulation in keratinocytes, increased proliferation of the basal layer, and increased the number and height of epidermal rete ridges [39]. Of interest, multiscale mechanical characterization of human foot skin, tested using computational models of load bearing, demonstrated that the enhanced resistance of plantar skin to deformation and stress-induced injuries is linked to its dermal and epidermal layer composition rather than to its greater interdigitation pattern [40]. This shows that all cutaneous compartments are involved in the overall high resistance of the plantar tissue to deformation.…”
Section: The Dej Undulating Pattern and The Rete Ridgesmentioning
confidence: 99%
“…Moreover, by varying the depth and force of indentation, it is possible to inspect the stiffness of subcellular structures such as the lipid bilayer, cornified envelope, cytoskeleton, and nucleus (Laly et al, 2021;Milani et al, 2018). Complementing the in vitro cellular studies, AFM has also been employed to map the elastic moduli across the different layers of plantar and nonplantar skin in a crosssectionally cut tissue, and the plantar skin cells of the stratum corneum, epidermis, and dermis were shown to be stiffer and less deformable (Boyle et al, 2019). Furthermore, the thickness of the stratum corneum positively correlated with increased protection from stress-induced injury.…”
Section: Applications Of Afm In Skin Science and Dermatologymentioning
confidence: 99%
“…The strength and resilience of the skin tissue are crucial for this protective function, and its biomechanical properties arise from a complex interplay between the cellular and molecular components. Whereas extracellular matrix proteins, such as collagen and elastic fibers, confer strength and flexibility to the dermis, differentiated keratinocytes (KCs) in the epidermis create a tough barrier in the outermost layer of the skin (Boyle et al, 2019). Cellular mechanosensing within the skin also plays important roles in tissue homeostasis and repair through the regulation of fundamental biological processes such as growth, migration, and differentiation, and these responses are mediated by the cell's mechanical properties and mechanotransduction machinery (Biggs et al, 2020).…”
Section: Introductionmentioning
confidence: 99%